Pianista colaborador: a formação e atuação performática voltada para o acompanhamento de flauta transversal - Adriana Abid Mundim (2009)
This dissertation focuses on the different roles played by the collaborative pianist, discussing his/her formation in the academic milieu, the terminology employed to refer to his/her specialization in the work environment, the assessment of his/her skills and abilities. We use as reference the follow up of the flute and its repertoire with the piano. Firstly we contextualize the collaborative pianist throughout the different periods of the History of Music, by reviewing the bibliography on the subject. We also prepared questionnaires that were sent to collaborative pianists and to piano and flute professors so as to assess the main questions involved in the formation and qualification of the collaborative professional in the Brazilian market. During the research we confirmed that this kind of professionals is in great demand in music teaching institutions. Disklavier is pointed out as an alternative tool that can help in the study and preparation of players and singers, but which does not substitute the pianist in actual performances. We conclude that the collaborative pianist's studies are done empirically, since no specific degrees are on offer in Brazilian academic institutions.